Statistics and occupational health: basic statistics concepts / Estadística y salud en el trabajo: conceptos básicos de estadística - Soto Espinosa, Juan Luis (Red de Investigación en Salud en el Trabajo; Vol. 2 Núm. 3 (2019), 2019)
Statistics is the discipline that is responsible for the collection, organization, analysis and presentation of data from the study of natural, social phenomena or productive, administrative, health processes among many others. This discipline aims to understand, with a certain degree of confidence, the behavior of the variables under study and to create models that allow predicting future conditions based on the behavior of the data collected. In this first installment, basic concepts of the discipline are presented, essential for the reader interested in the area to enter this field and deepen the use of techniques and tools for the analysis of data that will be presented in future deliveries.